Revealing EFL Teachers' Experiences in the Integration of Web-based Assessment Media for Assessment - Bulqiyah, Suhaimah; Munir, Ahmad (Journal of English Teaching and Learning Issues, 2023)
This study presents the integration of web-based assessment media for assessment in EFL online classrooms from the teachers’ points of view. This study aimed at exploring their experiences in online assessment using various web-based media. Additionally, this research shows both excellent and limited characteristics of web-based platforms implemented in online assessment as well as the influences on their teaching praxis. Five high school teachers from two different areas were invited to the online interview. This study found that the selected online media used by the teachers in their assessment are based on personal reasonings such as the features, form of assessment, and forth. the technology adoption to language assessment also explicitly indicates positive impacts on teachers’ professional affairs, particularly in the assessment field. The same effects are also reflected in students’ learning environment that makes them more involved in online learning and gets valuable assessment. The findings of this research have contribution to the development of assessment media for both English instructor and web-developer.